HDAC7 induction combined with standard-of-care chemotherapy provides a therapeutic advantage in t(4;11) infant B-cell acute lymphoblastic leukemia - Oriol de Barrios; Ingrid Ocón-Gabarró; Mar Gusi-Vives; Olga Collazo; Ainara Meler; Paola A. Romecín; Alba Martínez-Moreno; Juan Ramón Tejedor; Mario F. Fraga; Pauline Schneider; Michela Bardini; Giovanni Cazzaniga; et al. (Biomarker Research)
Abstract Background Infants diagnosed with B cell acute lymphoblastic leukemia (B-ALL) and t(4;11) chromosomal rearrangement display poor therapeutic response, associated to the low expression of B lymphocyte factor HDAC7. This study was conceived to identify a therapeutic strategy for t(4;11) B-ALL that restores optimal HDAC7 expression. Methods A multiomics approach in a large infant pro-B-ALL cohort was employed to identify HDAC7’s repression mechanism. These data, combined with cell culture assays in a variety of pro-B-ALL cell lines with differential HDAC7 levels, led us to define a novel combination therapy. Murine leukemia models and ex vivo assays using patient-derived xenografts (PDX) were employed to assess the benefits of this therapy when incorporated to glucocorticoid-based chemotherapy. Results Our data demonstrates that HDAC7 is epigenetically silenced by EZH2 and KMT2A::AFF1 fusion protein. Remarkably, the Menin-1 inhibitor MI-538 restores HDAC7 expression, and the effect is enhanced by class I HDAC inhibitor chidamide. This treatment drives leukemic pro-B cells towards a more differentiated state and impairs aberrant proliferation in an HDAC7-dependent manner. This newly identified therapy increases glucocorticoid sensitivity of PDX cells ex vivo, by repressing RUNX2 transcription factor. Finally, combining MI-538 and chidamide with standard chemotherapy reduces PDX cells engraftment in vivo and delays relapse. Conclusions The combined therapy proposed, based on Menin-1 inhibition, improves t(4;11) B-ALL cells’ response to standard therapy, an effect partially mediated by HDAC7 induction. Therefore, this novel therapy opens a new field for personalized treatments in high-risk leukemia, especially for infants presenting low expression of HDAC7 B cell factor.